Integration of CT urography improves diagnostic confidence of 68Ga-PSMA-11 PET/CT in prostate cancer patients - Will, Leon; Giesel, Frederik L.; Berger, Anne Katrin; Mier, Walter; Körber, Stefan A.; Rathke, Hendrik; Kremer, Christophe; Kratochwil, Clemens; Kauczor, Hans-Ulrich; Haberkorn, Uwe; Weber, Tim (Cancer imaging, 2017)
To prove the feasibility of integrating CT urography (CTU) into 68Ga-PSMA-11 PET/CT and to analyze the impact of CTU on assigning focal tracer accumulation in the ureteric space to either ureteric excretion or metastatic disease concerning topographic attribution and diagnostic confidence.
Die Zahl 68 ist im Titel hochgestellt
Gesehen am 21.06.2018